Microwave-Assisted Synthesis of (±)-Mandelic Acid-d5, Optical Resolution, and Absolute Configuration Determination - Claudio Bruno; Giovanni Lentini; Angelo Lovece; Maria Maddalena Cavalluzzi; Alessia Carocci; Alessia Catalano; Carlo Franchini (Journal of Chemistry)
An efficient microwave-assisted synthesis of (±)-mandelic acid-d5 was developed. The racemic mixture was resolved by diastereomeric salt formation using 1-phenylethylamine enantiomers as resolving agents. At each step, the resolution process was checked by determining mandelic acid-d5 enantiomer ee values directly on fractional crystallized diastereomeric salts by chiral capillary electrophoresis analysis. Highly enriched (−)- and (+)-mandelic acid-d5 (95% and 90% ee, resp.) were obtained and their absolute configurations—R and S, respectively—were determined by correlation of the (−)-mandelic acid-d5 circular dichroism spectrum to the (R)-mandelic acid one.